Failures in Reinforced-Concrete Columns and Proposals for Reinforcement Solutions: Insights from the 2023 Kahramanmaraş Earthquakes - Ercan Işık; Dorin Radu; Ehsan Harirchian; Fatih Avcil; Enes Arkan; Aydın Büyüksaraç; Marijana Hadzima-Nyarko (Buildings)
Türkiye, a country that suffers significant structural damage from earthquakes, was struck by two major quakes on 6 February 2023, centered in Pazarcık (Mw = 7.7) and Elbistan (Mw = 7.6) in Kahramanmaraş. These earthquakes caused extensive damage and destruction to urban concrete structures, significantly contributing to the loss of life. Inadequate designs in columns, which are meant to maintain structural integrity and transfer forces, were a primary cause of the structural damage. This study provides information about these catastrophic earthquakes, focusing on the detailed examination of damages in reinforced-concrete (RC) columns. Structural analyses were conducted on a selected RC building, taking into account the primary causes of column damage: low-strength concrete and insufficient transverse reinforcement. Five different concrete classes and two transverse reinforcement spacing options were considered to analyze the impact of concrete strength. To address the exceeded shear forces in the columns, a fiber-reinforced polymer (FRP) wrapping method was employed for strengthening. Initially, a reinforcement analysis was performed on a single column that exceeded shear force limits, followed by strengthening applications on all columns exceeding the limit shear force. The results demonstrated that carbon fibers have a significant impact on the shear forces in columns. The conclusion of the research is that FRP increases the ductility of concrete columns, enabling them to withstand seismic forces more effectively. This is vital in ensuring the integrity of structures in earthquake-prone areas. Using FRP materials can also significantly reduce the carbon footprint associated with concrete construction by minimizing the need for maintenance and extending the lifespan of structures. FRP presents a sustainable and effective solution for addressing failures in reinforced concrete columns. Its unique properties not only enhance strength and durability but also significantly improve the resilience of structures against corrosion, seismic events, and overload conditions.